Speech and Language Support System for Children with Hearing Impairment - Kyriacou, Efthyvoulos C.; Mavrocheilos, Rafail; Nikolaou, Chrysovalantis; Charalambous, Marina; Hadjichristofi, George; Matziari, Elena; Ioannou, Maria (My University, 2016)
This study presents a system to support and monitor speech and language development in children with hearing impairment using hearing aids or cochlear implants or children with language delays. The idea is to support children at home, as well as during sessions with their speech therapists or teachers. The system is based on a set of applications for Android devices, Microsoft Windows computers, and Windows mobile devices. The applications were created as games, where the users are able to go through the four levels targeted (auditory skills, receptive language, expressive language, and speech / articulation) during speech and language support sessions. Results from the system are recorded on a server where specialists can monitor every child’s performance. This information can be used by specialists to pinpoint and address specific problems with subjects’ development. Applications that partially cover all four levels of the training procedure have been completed. They have been tested with a small group of users and specialists, and received very encouraging initial feedback.
Keywords: Speech; Language; Development; Support; Apps